Some Results on PIN and ITO Photodiodes - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
In this paper, various contributions concerning generalized photodiodes and ITO photodiodes are reported. In particular, calculations related to the bandwidth of the equivalent circuit ot a PIN photodiode are performed and compared to experimental considerations. In addition, an ITO structure on a layer n-type GaAs is examined. An ITO-HEMT is also considered.